Sosialisasi dan Penyuluhan Sadar Wisata Pada Pengembangan Kampung Wisata Baluwarti Sebagai Kampung Wisata Menuju Pariwisata Budaya di Kota Surakarta - Marimin Marimin; Deria Adiwijaya; Nanang Wijayanto; Jimmi Prasetyo; Tommi Afgiyanto (Politeknik Pariwisata NHI Bandung, 2020)
ABSTRACT Tourism is part of the field of economic activity that has a multiplier effect, not only providing benefits locally but also nationally, regionally and even globally. At this time, tourism has become a livelihood for the community. The national tourism policy is handed down to the provincial, city-regency and local governments. Implementation and execution of the program must start from the predetermined destination site environment, namely tourism awareness for the community. Baluwarti Village, Baluwarti Sub-District, Pasar Kliwon District, Surakarta City, is an important part of the main destination supporting the international-standard Surakarta Kasunanan Palace. The level of tourism awareness that has not been understood needs to be socialized through the Sapta Pesona concept. Tourism actors are expected to be professional in handling visitors through guides, developing palace area destinations, fulfilling hospitality and synergizing between departments in tourism activities.